TRANSDUCERS 2009 - 2009 International Solid-State Sensors, Actuators and Microsystems Conference 2009
DOI: 10.1109/sensor.2009.5285400
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte count and two-part differential in whole blood based on a portable microflow cytometer

Abstract: This work demonstrated leukocyte count and two-part leukocyte differential from the whole blood based on a portable microflow cytometer system. Leukocytes are selectively stained with a fluorescent dye, Acridine Orange (AO). The blood sample is then pumped through a disposable microfluidic device for fluorescence sensing. Under blue LED excitation (460nm), the green fluorescence from DNA and the red fluorescence from RNA are detected simultaneously with two photomultiplier tubes (PMT). Leukocytes are counted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…A group from CalTech has tested a microfabricated flow cytometer in microgravity during parabolic flight (Shi et al, 2009). The authors demonstrated leukocyte count and two-part differential (lymphocyte vs non-lymphocyte) counts from a blood sample.…”
Section: Space Travelmentioning
confidence: 99%
“…A group from CalTech has tested a microfabricated flow cytometer in microgravity during parabolic flight (Shi et al, 2009). The authors demonstrated leukocyte count and two-part differential (lymphocyte vs non-lymphocyte) counts from a blood sample.…”
Section: Space Travelmentioning
confidence: 99%
“…Cell counting was also assessed on the ground and the Guava instrument underestimated leukocyte numbers. Another group at the California Institute of Technology tested a microfluidic system able to discrimination of lymphocytes in blood and demonstrated in parabolic flight that its performance was not affected by the absence of gravity . These previous studies confirmed the robustness of the sheathless and microfluidic approaches.…”
Section: Discussionmentioning
confidence: 78%
“…1, a two-color LIF detection scheme is adopted for the flow cytometer. A microfluidic channel is used as a flow cell, where dye-stained blood sample is measured for fluorescence emission [4]. The blood sample is illuminated by an excitation laser (488nm) at the sensing zone, and the emission is measured in two color ranges, green (510nm~560nm) and red (>590nm), which accommodate the emission peaks of FITC (520nm) and PI (617nm).…”
Section: Detection Principlementioning
confidence: 99%
“…For instance, the nucleic acid dyes stain all nucleuses of different leukocytes with similar affinity. In our previous work [4], we encountered this problem with Acridine Orange dye and could only do a two-part DLC (i.e., lymphocytes and neutrophils).…”
Section: Introductionmentioning
confidence: 99%